2021
DOI: 10.3390/molecules26072010
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Cs-Based Pb-Free Double Halide Perovskites: From Theoretical and Experimental Studies to Doping and Applications

Abstract: Despite the progressive enhancement in the flexibility of Pb-based perovskites for optoelectronic applications, regrettably, they are facing two main challenges; (1) instability, which originates from using organic components in the perovskite structure, and (2) toxicity due to Pb. Therefore, new, stable non-toxic perovskite materials are demanded to overcome these drawbacks. The research community has been working on a wide variety of Pb-free perovskites with different molecular formulas and dimensionality. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 146 publications
0
18
0
Order By: Relevance
“…At present, there is considerable interest in the properties of the non-toxic double perovskite (elpasolite) systems and their applications, such as in solar energy conversion 1–3 and broad band white light emission. 4 Our study concerns one bismuth member of this family, and our aim is to provide a consistent and comprehensive explanation of the unusual and previously varied and contradictory observations and assignments of its optical behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is considerable interest in the properties of the non-toxic double perovskite (elpasolite) systems and their applications, such as in solar energy conversion 1–3 and broad band white light emission. 4 Our study concerns one bismuth member of this family, and our aim is to provide a consistent and comprehensive explanation of the unusual and previously varied and contradictory observations and assignments of its optical behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, although perovskites exhibit excellent optoelectronic properties, their poor stability and toxicity are the main challenges that need to be overcome for their industrial application, which requires further study and optimization of these materials. [7][8][9] Commonly proposed strategies to improve the stability of perovskites include the replacement of their A-site organic groups with inorganic metal cations (e.g., Cs, K, and Rb), [10][11][12][13] reduction of perovskite dimensions 14,15 and surface passivation. [16][17][18] Cesium-based double perovskites have been commonly reported in recent studies, 11,[19][20][21] with a remarkable improvement in thermal stability and high carrier mobilities.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Commonly proposed strategies to improve the stability of perovskites include the replacement of their A-site organic groups with inorganic metal cations (e.g., Cs, K, and Rb), [10][11][12][13] reduction of perovskite dimensions 14,15 and surface passivation. [16][17][18] Cesium-based double perovskites have been commonly reported in recent studies, 11,[19][20][21] with a remarkable improvement in thermal stability and high carrier mobilities. 22 Thus, experimental and theoretical investigations on Cs-based compounds are mainly discussed herein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This involves ultraviolet -NIR downshifting and the NIR emission is very weak in the perovskite CsPbCl 3 :Er 3+ . 19 Concerning the relevant literature, we are aware of a previous review of Bi 3+ -Ln 3+ co-doped double perovskites 20 and a study of Bi-Er co-doped Cs 2 AgInCl 6 7 for which white light was observed. The electronic absorption and emission spectra of the double perovskite (elpasolite) Cs 2 NaErCl 6 have previously been reported.…”
mentioning
confidence: 99%